The 1988-1989 VSC Lady Blazers - Valdosta State University, Athletics Department (Valdosta State University, 1989)
Shannon Williams,Valdosta States fifth Kodak all- American,is pictured with Lady Blazer head coach Charles Cooper,who has coached the last three players to reach all-American status. Williams,a junior,was the player of the year in the Gulf South Conference a year ago and was a member of every post-season team picked by various publications. The photo and others in this brochure were taken by college photographer Derek Pickup.
### Staff Deborah McBeath; Charles Cooper; Gretchen Browne; Tommy Thomas; Kathie Gardner; Tom Bair; Amanda Watson; Steve Roberts; Robert Bohler; Russ Beckham; Larry Lampert; ### Players: Becky Hays; Melissa Spooner; Molly Baker; Becky Wallace; Shannon Williams; Beth Clark; Laine Scarborough; Carol Bradley; Verdell Kenon;
Keywords: Athletics; Basketball; Lady Blazers